Motion analysis for sport performance (2006)
Motion Imaging Corporation`s line of Motion Analysis software is capable of integrating a variety of cameras and configurations, offering a complete solution for capturing and analyzing sport activities as they occur on the playing field or in a laboratory setting. In the field, whether it is used as a coaching tool or for research, DMAS6 permits camera control and capture by utilizing a laptop and camera system to quickly analyze motion.